A Historical Public Debt Database. (IMF Working Papers; Working Paper, 2010)
This paper describes the compilation of the first truly comprehensive database on gross government debt-to-GDP ratios, covering nearly the entire IMF membership (174 countries) and spanning an exceptionally long time period. The database was constructed by bringing together a number of other datasets and information from original sources. For the most recent years, the data are linked to the IMF World Economic Outlook (WEO) database to facilitate regular updates. The paper discusses the evolution of debt-to-GDP ratios across country groups for several decades, episodes of debt spikes and reversals, and a pattern of negative correlation between debt and growth.